Evaluation of sugar content in probiotics products prescribed for children - a review - KUMAR. S, PRAVEEN; SUBRAMANIAN, EMG.; SIVASAMY, VINAY (The journal of contemporary issues in business and government, 2021)
The interest in nutritional supplement and functional food has risen significantly in recent years. Many of the products that are marketed to the consumers have the benefits of the probiotic for general good health and for a wide variety of conditions and situations. Although most of the products have been used safely for years, careful analysis and see scientific research should be conducted before routinely recommendation these products, especially for children.A basic understanding of intestinal flora, properties of probiotic and clinical research findings is necessary for clinicians to delineate probiotic agents in paediatric population. Therefore, the aim of this paper will be to summarize available evidence of probiotic use in well-defined clinical indications of importance for pediatricians. Sweetened oral medications are widely used for children to facilitate compliance. A variety of natural and artificial sweeteners are used in these drug formulations to augment the sweetness and thereby palatability of the product. There is growing concern among dentists about the increased consumption of sugars in these medications by children, especially those who are chronically ill as it may contribute to diabetes mellitus, dental erosion, and dental caries. This literature review provides information about the sweetener content and cariogenic potential of commonly prescribed pediatric oral medications that are used for managing acute and chronic conditions in children and measures for oral health prevention.